The Utility of ERBB4 and RB1 Immunohistochemistry in Distinguishing Chromophobe Renal Cell Carcinoma From Renal Oncocytoma. (May 2020) - Sun, Tong; Hutchinson, Lloyd; Zhou, Amy G.; Liu, Qingqing; Cosar, Ediz F.; St. Cyr, Maryann; Ninteau, Nicole; Dresser, Karen; Cheng, Liang; Jiang, Zhong; Cornejo, Kristine M.
Objectives . Differentiating renal oncocytoma (RO) from chromophobe renal cell carcinoma (ChRCC) can occasionally be challenging. We evaluated the expression of RB1 and ERBB4 in RO and ChRCC, and compared the immunohistochemistry (IHC) results to RB1 and ERBB4 gene abnormalities detected by fluorescence in situ hybridization (FISH). Materials and Methods. Fifty-three kidney resections (ChRCC, n=28; RO, n=25) were stained for RB1 and ERBB4 IHC and FISH was performed to evaluate gene copy number analysis. Results. A loss of RB1 staining was identified in 64% (18/28) of ChRCCs, which was not found in any ROs (0/25; P <.001). FISH analysis revealed 36% (10/28) of ChRCCs contained a RB1 hemizygous deletion with a concordance of 56% (10/18) between the IHC and FISH findings. No RB1 gene copy number variations were detected in any of the ROs (0/25; P <.001) and retained expression of RB1 by IHC. ERBB4 showed cytoplasmic/membranous staining in all ROs and ChRCCs. However, 75% (21/28) of ChRCCs also contained nuclear positivity for ERBB4, which was uncommonly seen in ROs (3/25, 12%; P < .001). A hemizygous ERBB4 gene deletion was detected in 46% of ChRCCs (13/28), but none of the ROs (0/25; 0%). Loss of labeling by RB1 or nuclear staining for ERBB4 IHC identified 25 of 28 (89%) of ChRCCs. Conclusion. In summary, the loss of RB1 expression is a highly specific diagnostic biomarker in distinguishing ChRCC from RO. Nuclear ERBB4 expression also appears to be a sensitive diagnostic biomarker for ChRCC, albeit the mechanism is unknown.